Acute effects of progressive sled loading on resisted sprint performance and kinematics - Pareja-Blanco, F.; Pereira, L. A.; Freitas, T. T.; Alcaraz, P. E.; Reis, V. P.; Guerriero, A.; Arruda, A. F. S.; Zabaloy, S.; Saez De Villarreal, E.; Loturco, I. (The Journal of Strength and Conditioning Research, 2022)
We examined the effects of 5 loading conditions (0, 20, 40, 60, and 80% of body-mass [BM]) on resisted sprint performance and kinematics in male rugby players over different distances. Ten players from the Brazilian National Team (20.1 ± 3.3 years; 88.7 ± 18.8 kg; 178.3 ± 6.2 cm) performed 20-m sprints under the 5 loading conditions. Sprint times in 5, 10, and 20 m were recorded. Stride length (SL), and hip, knee, and ankle angles were measured using an eight-sensor motion analysis system. The kinematic parameters were calculated over the different distances. Heavier loads led to significantly greater velocity loss (p < 0.001-0.05). Significant reductions in SL were also observed when comparing 0% BM and all resisted sprints in all assessed distances (p < 0.001-0.05, effect size [ES]: 1.35-4.99). Very heavy (80% BM) sled load provoked significantly greater decreases in SL than the rest of loading conditions (p < 0.01-0.05). Important kinematic alterations were observed for all loading conditions and sprint distances when compared with 0% BM (ES: 0.76-1.79, for hip-angle; 0.20-1.40, for knee-angle; and 0.73-1.88, for ankle-angle). Moreover, 80% BM induced significantly higher hip flexion, lower knee flexion, and higher ankle dorsiflexion than 20% BM condition at 5-10 and 10-20 m distances (p < 0.05). Lighter sled loads (<40% BM) seem to be more adequate to improve speed ability without provoking drastic changes in the unloaded sprinting technique, whereas heavier loads may be more suitable for optimizing horizontal force production and thus, acceleration performance.